p+9=4p-12

Simple and best practice solution for p+9=4p-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for p+9=4p-12 equation:


Simplifying
p + 9 = 4p + -12

Reorder the terms:
9 + p = 4p + -12

Reorder the terms:
9 + p = -12 + 4p

Solving
9 + p = -12 + 4p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-4p' to each side of the equation.
9 + p + -4p = -12 + 4p + -4p

Combine like terms: p + -4p = -3p
9 + -3p = -12 + 4p + -4p

Combine like terms: 4p + -4p = 0
9 + -3p = -12 + 0
9 + -3p = -12

Add '-9' to each side of the equation.
9 + -9 + -3p = -12 + -9

Combine like terms: 9 + -9 = 0
0 + -3p = -12 + -9
-3p = -12 + -9

Combine like terms: -12 + -9 = -21
-3p = -21

Divide each side by '-3'.
p = 7

Simplifying
p = 7

See similar equations:

| (-(x-4)(x-4))=0 | | 8x-6+x-1=13 | | 3y=7+15 | | 8(k-3)=32 | | 4j-3j= | | (n+4)*9=72 | | 4s-13=15 | | (n-7)*3=12 | | 42x+3=43x | | (n+2)*5=20 | | 7x-1=3(x+2) | | 4a-1a=4 | | 4a-1a=4# | | 4-3(x+1)=10 | | 31x+4=128 | | -2(-x-4)=-2x+4 | | 9-3(2+y)=9 | | 8(4+y)=7(y-6) | | x+106=100 | | 260-5X=40X+20 | | p-2p=18 | | x^2-10x=-8 | | 1.005xn=2 | | 3x+2=-2x-28 | | 6(c+1)=5+5c | | 4(2x+3)=3x-(2x-2) | | 10(3-x)=-4x-6 | | 2a+8=54 | | -12=-5-6x+11 | | D+-8d+7=0 | | 2x+12+6x-10=180 | | -0.06y+0.08(1100-y)=0.36y |

Equations solver categories